nal fissure: Chemical or surgical sphincterotomy? Prospective analysis of 98 patients - Alonso, Oscar; Piñeiro, Santiago; Cazabán, Luis; Misa, Ricardo (Cirugía del Uruguay, 2006)
Introduction: Anal fissures are a frequent cause of consultation, be it at the general surgery hospital or in the proctology service. A better acquaintance with ano-rectal physiology and physiopathology have resulted in a change in therapy of this pathology. Objective of paper: to evaluate the various alternative therapies in a group of patients with anal fissure.